Physical activity in patients with haemophilia - advantages and prophylaxis. Current trends - Jędrzejewska-Rzezak, Patrycja (Quality in Sport, 2025)
Hemophilia is the most prevalent severe hereditary hemorrhagic disorder. Severe hemophilia symptoms encompass recurrent joint bleeding that can result in degenerative arthropathy. The manifestation of hemophilic arthropathy symptoms markedly diminishes the quality of life for affected patients and considerably restricts their social functioning. The approach to treating hemophilia has been transformed, focusing on preventing hemophilic arthropathy and helping patients lead normal lives alongside healthy individuals. Historically, involvement in sports was discouraged because to the elevated chance of injury and subsequent hemorrhaging; however, contemporary medical understanding advocates for sports engagement to enhance physical and social well-being. Prophylaxis effectively sustains a minimum level of clotting factor activity, enabling people with hemophilia to engage regularly in sports activities. Aim of the study: The fundamental objective of this research is to clarify the latest management concepts related to hemophilia. Considerable emphasis is placed on the significance and safety of physical activity for persons affected by this disease. Materials and methods: A review of the literature available in the PubMed and Google Scholar database was performed, using the key words: “hemophilia”, “prophylaxis”, “physical activity”, “gene therapy”, “hemophilic arthropathy”. Conclusion: Advancements in treatment have increased the life expectancy of those with hemophilia, and the need to optimize health is underscored through preventing chronic conditions and promoting regular physical activity. Recent evidence indicates that physical activity is advantageous and safe in this condition. Additional study is required to formulate specific suggestions for patient education and enhance their long-term quality of life.